An enhanced sub-image encryption method. (November 2016) - Wang, Xing-Yuan; Zhang, Ying-Qian; Liu, Lin-Tao
Abstract: Recently a parallel sub-image encryption method is proposed by Mirzaei et al., which is based on a total shuffling and parallel encryption algorithm. In this paper, we firstly show that the method can be attacked by chosen plaintext attack and then propose an enhanced sub-image algorithm, which can completely resist the chosen plaintext attack. Moreover, our improved algorithm can reduce the encryption time dramatically. The experimental results also prove that the improved encryption algorithm is secure enough. So the improved method can be used in image transmission system.